Spectral characterization and discrimination of sorghum (Sorghum bicolor (L.) Moench) cultivars for remote sensing-based phenotyping and selection - Chidoko, Pardon; Mhike, Xavier; Chemura, Abel; Manyanga, Munyaradzi (Springer Nature, 2025)
Remote sensing has immense potential for high throughput phenotyping of agronomic and physiological traits that can be used in the selection of elite lines for productivity and adaptability in crop breeding programs. This is critical for important crops such as sorghum that are important for food security and livelihoods of millions of people in the world. The aim of this study was therefore to use remote sensing for spectral characterization and discrimination of 20 sorghum cultivars that are produced and grown in Southern Africa. Spectral reflectance indices (SRIs) were used in detecting variations in morphological traits (leaf length, leaf width, leaf area, plant height, number of leaves and chlorophyll) at vegetative and maturity growth stages. Our results showed that the morphological traits were all higher at maturity stage than at vegetative stage as expected but varied widely between the evaluated cultivars. Of the 29 indices, 12 and 19 of the evaluated vegetation indices showed significant differences between cultivars (p < 0.05) at vegetative and maturity stages, respectively. There was a significant relationship (p < 0.05) between morphological traits and SRIs, which were dominantly moderate at both stages. There were distinct differences between hybrids and open-pollinated (OPVs) varieties at maturity stage, with high reflectance observed from OPVs in the visible and near-infrared regions of the spectrum. Three principal components identified four indices with high discrimination ability among sorghum genotypes. We conclude that there is great potential for spectral data to be used in phenotyping and cultivar selection in sorghum crop improvement.